Valorization of Vase Dam by the addition of the cement kiln Dust (CKD) - Bensalem, Ahmed; Mellas, Mekki (Journal of Applied Engineering Science & Technology; Vol 4 No 2 (2018): Issue In Progress, 2018)
This study is the valuation of the mud dam Charef - Djelfa Wilaya in basic layers of material by the chemical stabilization process based on the addition of cement kiln dust (CKD) who considered under product from the manufacture of cement. In this context we came through particle size analysis tests, plasticity, chemical analysis, compaction, and simple compression on different samples of mud treated with different percentages of CKD and stored at a period of 28 days to change the consistency of the untreated mud and was a firm consistency to a hard and stable consistency by adding a percentage of 20% CKD.